Testing Measurement and Factor Structure Invariance of the Physical Activity and Leisure Motivation Scale for Youth Across Gender - Kueh, Yee Cheng; Abdullah, Nurzulaikha; Kuan, Garry; Morris, Tony; Naing, Nyi Nyi (Frontiers in Psychology, 2018)
Measurement equivalence is often assumed across comparison groups, a pervasive problem related to many self-report instruments. Measurement equivalence, also known as measurement invariance, implies that a measure has the same meaning across different groups of people. In this study, we aimed to examine the measurement and structural invariance among gender of the Malay version of the Physical Activity and Leisure Motivation Scale for Youth (PALMS-Y-M). Seven-hundred-and-eighty-three secondary school students (female = 57.3%, male = 42.7%) with mean age 14.5 years (SD=1.25) from Kota Bharu, Malaysia, volunteered to participate in this study and completed the PALMS-Y-M, consisting of 28 items with seven subscales. We conducted the confirmatory factor analysis (CFA) and invariance tests on the seven motives of the PALMS-Y-M model. The hypothesised model consisted of 28 observed items and seven latent variables. We used estimator robust to maximum likelihood, MLR to examine the hypothesised measurement and structural invariance. Measurement invariance was tested for three different levels. We first established the configural invariance model, then we compared the metric invariance model and the scalar invariance model with the less restrictive model. Then structural invariance was tested for factor variance, covariance and means. Findings provided evidence for full measurement and structural invariance of the PALMS-Y-M in males and females. The final CFA model fit the data well for males (CFI = .922, RMSEA = .048, SRMR = .050) and females (CFI = .922, RMSEA = .047, SRMR = .053). When invariance of both factor loadings and item intercepts holds in PALMS-Y-M, underlying factors consisting of different motives for participating in PA can be meaningfully compared across gender. Accurate and valid measurement of PALMS-Y-M across comparison groups is crucial for future research that involves examining motives to physical activity in different genders and other socio-cultural variables.